The Urgency of Takaful-Based Protection for Gig Workers through Pentahelix Model - Muhammad Al Berto; Andriani Samsuri; Muhammad Daffa Al-farisy (Program Studi Magister Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Sunan Kalijaga, 2025)
This study highlights the urgency of implementing a Takaful-based protection scheme to address the increasing vulnerability of gig workers within Indonesia’s rapidly expanding digital economy. The research aims to examine the opportunities and challenges of takaful implementation in the gig economy and to conceptualize a Pentahelix-based partnership model for developing an inclusive and sustainable Sharia-compliant insurance ecosystem. Using a qualitative descriptive approach with a conceptual strategy through library research, this study analyzes academic literature, regulatory frameworks, and institutional reports related to takaful, social protection, and platform-based labor. The findings indicate that despite the steady growth of the takaful sector in Indonesia, takaful penetration among gig and informal workers remains extremely low. Limited takaful literacy, weak digital integration, and insufficient cross-sectoral policy coordination is identified as the main constraints. To overcome these challenges, this study proposes a Pentahelix collaboration model involving government, academia, industry stakeholders, communities, and media to strengthen literacy, encourage product innovation, and improve institutional coordination. This study contributes to policymaking by offering a collaborative framework for integrating takaful into Indonesia’s gig economy ecosystem and provides strategic insights for key policymakers particularly in terms of regulatory coordination, incentive alignment, and data integration mechanisms. Furthermore, the proposed Pentahelix-based model serves as an operational reference for industry stakeholders and digital platforms in embedding Sharia-compliant protection schemes within platform-based work systems.